Bioactivity-guided isolation and chemical characterization of antiproliferative constituents from morel mushroom (Morchella esculenta) in human lung adenocarcinoma cells. (January 2018) - Lee, Seoung Rak; Roh, Hyun-Soo; Lee, Seul; Park, Hyun Bong; Jang, Tae Su; Ko, Yoon-Joo; Baek, Kwan-Hyuck; Kim, Ki Hyun
Graphical abstract: Highlights: Morel mushroom ( Morchella esculenta ) is a wild edible mushroom. Bioactivity-guided isolation of the extract led to the isolation of eight compounds. Compounds1 and3 –7 were isolated for the first time from M. esculenta . Compounds1, 3, and5 exhibited potent cytotoxicity to human lung cancer cells. The activity of compounds1, 3, and5 was mediated by the induction of apoptosis. Abstract: Morchella esculenta (Morchellaceae), one of the most widely appreciated wild edible mushrooms, has demonstrated antitumor activity both in vivo and in vitro . However, the molecular basis underlying its antitumor activity has not yet been elucidated. In this study, we examined the biological effects of the MeOH extract of M. esculenta fruiting bodies on four human lung adenocarcinoma cell lines. Bioactivity-guided fractionation of the MeOH extract followed by chemical investigation of its most cytotoxic hexane-soluble fraction led to the isolation of eight compounds (1  −8 ), including three fatty acids and five sterols. This is the first report of the isolation of compounds1 and3 –7 from M. esculenta . Among the eight isolated compounds tested, compounds1, 3, and5 exhibited the most potent cytotoxicity to human lung cancer cell lines, with IC50 values ranging from 156.9 to 278 M; this activity was mediated by induction of apoptosis.